The Lived experiences of cluster foster parents in caring for foster care children with special needs in Mpumalanga, South Africa - Manamela, Nakedi Presley; Rapholo, Selelo Frank; Singwane, Thembinkosi Peter (Penerbit Universiti Kebangsaan Malaysia, 2024)
The growing number of children in foster care has often overburdened the foster care system and the social development capacity in South Africa. Cluster foster care is a contemporary and unfamiliar system of foster care in South Africa which emerged, among others, due to the protracted and tedious process of placing children in foster care, in addition to vulnerable children. The increase of children with special needs has also exacerbated the desolate foster care system. That said, the understanding of cluster foster parents particularly those fostering children with special needs has been greatly affected by the dearth of literature and paucity of studies focusing on this domain. Hence the objective of this qualitative study. Through the phenomenological research design and the application of purposive sampling, 15 cluster foster parents were selected to participate in the study. Following some vigorous semi-structured interviews and the subsequent thematic analysis, the findings of the study revealed that cluster foster parents are faced with extreme challenges such as lack of support, knowledge, and limitation of resources in fostering children with special needs. This was worsened by the behavioural challenges exhibited by the challenges with special needs. Further findings revealed that Cluster foster parents continue to struggle to meet the basic needs of foster children in need of care and protection. Consequently, the study recommends the development of empowerment programmes, enhanced support mechanisms and ongoing holistic assessment of cluster foster parents to enable enriching and adequate care of foster children with special needs.